Pengaruh Life Style, Media Sosial TikTok, dan Kebutuhan Terhadap Penggunaan Shopeepay Later (Studi Kasus Mahasiswa Universitas Bojonegoro) - Praptiwi Diana Lestari; Endang Endang (Universitas Batanghari Jambi, 2023)
Innovations in the economic sector gave rise to online loans such as Shopeepay later which were easily accessible by several students which sparked the desire of students to always shop on the Shopee application because of the many demands on lifestyles from the environment, trends from social media such as Tiktok, to the basic needs they use . The large number of products sold at Shopee, ranging from relatively low prices to those that seem expensive, has created a desire to use Shopeepay later to make it easier for them to make transactions because of easy access and registration which is quite easy for students to do. The purpose of this study is to find out how much influence there is between variables, namely the influence partially by lifestyle variables, TikTok social media, and the need for using Shopeepay Later, and the simultaneous influence of these 3 variables affecting the use of Shopeepay Later on Bojonegoro University students, as well as variables the most dominant of the three variables in the use of Shopeepay Later. The type of research used is quantitative by using the questionnaire method with a sample of 100 respondents from the entire population of Bojonegoro University students. Using quantitative methods to easily test hypotheses, the sampling technique itself uses random sampling where the researcher distributed questionnaires via a google form. it is concluded that the research obtains results if Life Style (XI), Social Media (X2), and Needs (X3), have a partial effect on the Use of (Y) Shopeepay Later, then Life Style (XI). Social Media (X2), and Needs (X3) simultaneously influence the use of (Y) Shopeepay Later, and it can be seen that the most dominant result that influences the use of (Y) Shopeepay Later is Needs (X3).